Panpuzfape Media to Improve Thematic Learning Outcomes of Grade V Elementary School Students - I Nengah Arya Dana Putra; I Gusti Ayu Tri Agustiana; Kadek Ari Dwiarwati (Journal of Education Technology, 2023)
The lack of media used in learning can affect the low student learning outcomes. This study has four objectives, namely to produce a design of panpuzfape media on the theme of events in life, to analyze the validity of the content of panpuzfape media on life events, to analyze the practicality of students in panpuzfape media on the theme of life events, and to analyze the effectiveness of panpuzfape media development on the theme of deep events in order to improve the learning outcomes of fifth grade students in elementary schools. This development study uses the ADDIE model, which is composed of five stages, namely analysis, design, development, implementation, and evaluation. This study takes the subject of panpuzfape media, while the objects of development research are media content validity, user response, and media effectiveness. Data collection methods used are observation, interviews, questionnaires, and tests. The instruments used for data collection were observation guidelines, rating scale sheets, interviews, and questionnaires. Quantitative analysis method consists of two ways, namely descriptive statistics and inferential statistics. The results showed that Panpuzfape media was valid in terms of the results of the expert's assessment, practical in terms of the results of the practitioner's assessment, and effective in terms of the results of tests on students.